Resistance Behaviour of Quantum Tunneling Composite (QTC) Pill for Tactile Sensor Application / Nur Izzah Lina Azaman ... [et al.] - Azaman, Nur Izzah Lina; Ahmad, Ahsana Aqilah; Ayub, Muhammad Azmi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
A metal polymer composite known as Quantum Tunneling Composite (QTC) has ability of turning into a remarkable material for new era sensor. This is considering QTC material flexible, soft and has extraordinary electrical properties. Its resistance changes during compressing; thus, changing the way it conducts. This paper proposes two methods which are conducted based on the sensitivity of the QTC pill. The piezoresistive experimental test was performed by sandwich and side by side contact arrangement to determine the QTC pill resistivity characteristics and suitability tactile sensor. The result shows that the QTC pill resistance of sandwich and side by side contact arrangement values dramatically drop at the beginning, and then start stabilized at point 4.903N and 5.884N respectively. From the exponential curve graph obtained through resistance versus force (R vs. F) investigation, it shows QTC pill is a good insulator as well as a good conductor when compressed. Based on this investigation, QTC pill provides benefit in developing tactile sensor with its capability to increase the conductivity of the metal polymer composite under mechanical deformations until a certain force.